Determination of FAM72 Family Proteins as Poor Prognostic Markers in Clear Cell Renal Carcinoma - Gou, Hui; Chen, Ping; Wu, Wenbing (Recent Developments in Chemistry and Biochemistry Research Vol. 3, 2024)
Purpose: This study aimed to investigate the prognostic significance of the Family with Sequence Similarity 72 member (FAM72) gene family in clear cell renal carcinoma (ccRCC) using a bioinformatic approach. Background: The Family with Sequence Similarity 72 (FAM72) gene family, specific to neural stem cells, has emerged as a potential biomarker in various cancers, including glioblastoma multiforme, adrenocortical carcinoma, and lung adenocarcinoma. Methods: We conducted an analysis of FAM72 expression levels in ccRCC tissues and normal kidney tissues using TCGA data. We performed univariate and multivariate Cox regression analysis to assess the prognostic value of FAM72 expression. Furthermore, to find enriched biological processes connected to FAM72 expression, Gene Ontology (GO) and Gene Set Enrichment Analysis (GSEA) were used. We also examined the degree of methylation and immune cell infiltration in patients with ccRCC. Results: Our bioinformatic analysis revealed that FAM72 expression levels were significantly higher in ccRCC tissues than in normal kidney tissues. High expression of FAM72 was associated with poor prognosis in ccRCC patients and was found to be an independent prognostic factor for ccRCC. GO and GSEA analyses indicated that FAM72 was enriched in biological processes related to mitosis, cell cycle, and DNA metabolism. Moreover, a significant correlation was found between FAM72 and immune cell infiltration and the level of methylation in ccRCC patients. Conclusion: Our findings suggest that FAM72 could serve as an unfavorable prognostic molecular marker for ccRCC. A comprehensive understanding of FAM72 could provide crucial insights into tumor progression and prognosis. The results not only contribute to the understanding of FAM72's role in ccRCC but also pave the way for future research aimed at exploring the therapeutic potential of targeting the FAM72 gene family. The development of targeted therapies that modulate FAM72 expression or function could offer a novel approach to improving treatment outcomes for ccRCC patients.